Hyper-fortunes and the super-rich: Why a wealth tax makes sense - Ramon E. López; Gino Sturla Zerene (CEPAL Review, 2021)
This article proposes a model to estimate the wealth of the richest groups in society and to design an efficient wealth tax system. For design and implementation issues, it reviews comparative international experience and provides an analytical discussion of the effects of a wealth tax, reviewing the main criticisms that orthodox economists have levelled against it. The methodology used to calculate wealth involves first-order approximations and Pareto criteria to compensate for data shortcomings. This article also presents a tax system which corrects the problems that have arisen when implementing this type of tax in other countries. The model is applied to the reality of Chile, which, like other countries in the region, suffers from structural inequality in both income and wealth, which has been amplified by the effects of the COVID-19 pandemic.